Reflexión sobre factores causales de la violencia de género - Gòmez Arèvalo, Dany Alejandra; Torres Escobar , Germán Andrés (Uptc, 2024)
The present reflection article intends to describe the concept of gender violence and some of its main causal factors, which are: sexist beliefs, the lack of adequate emotional and sexual education, and hypersexuality. After analyzing each of these causes, it was established that it is relevant for educational institutions to offer comprehensive sexual education that helps students improve their understanding of their own sexuality and affectivity, and it is also relevant for these institutions to develop training strategies aimed at parents, teachers and administrative staff, in order to raise awareness about the phenomenon of gender violence, its prevention and reporting.